Les énergies renouvelables face à leur territorialisation : une mise en parallèle France-Allemagne par les systèmes d’acteurs - Philippe Hamman; Marie Mangold; Céline Monicolle; Patricia Schneider (VertigO)
This paper studies energy transition from the perspective of actors, through an analysis of the concrete territorialization processes involved in the development of renewable energy projects. It draws empirical comparisons between French and German situations based on sociological surveys conducted in the Upper Rhine region. First, we conducted interviews of key actors of the regional energy scene on both sides of the Rhine, with 26 German and 30 French respondents. Then we used the software Alceste on the two sets of interviews in order to identify, through statistical and lexical analysis, the interactions and nodal issues in the field of renewable energies. As can be seen, the same type of topical questions were raised in both cases – questions about economic viability, technical possibilities and environmental acceptability – in relation to very diverse renewable energy projects. The study also showed that a plurality of institutional and noninstitutional actors – private or public actors as well as citizens – took part in the territorialization dynamics at work in renewable energy projects. The sectors involved, the barriers and levers for the projects appear to result from multi-scale interrelationships rather than deriving from one single model, neither designed at a local level nor developed in a global or top-down fashion.